MicroRNAs: Potential Targets in Diabetic Retinopathy - Li, Xin; Yu, Zi-Wei; Wang, Ying; Fu, Yu-Hong; Gao, Xin-Yuan (Hormone and Metabolic Research, 2020)
Diabetic retinopathy (DR), a serious microvascular complication of diabetes, is a leading cause of blindness in adults. The pathogenesis of DR involves a variety of tissues and complex mechanisms, such as inflammation, oxidative stress, optic neurodegeneration, and autophagy. Nowadays, microRNAs (miRNAs), a novel group of non-coding small RNAs, have been extensively studied and recognized to play a key role in the pathogenesis of DR through aforementioned pathways. Furthermore, some miRNAs have been proposed as biomarkers that may be utilized to screen for DR. Also, miRNAs are a new therapy for DR. In this review, we summarize several miRNAs and, their roles in the pathogenesis of DR. miRNAs, as potential pharmacological targets for the diabetic retinopathy, may provide new insights for the treatment of DR.
Keywords: microRNAs; diabetic retinopathy; biomarker; oxidative stress; inflammation; angiogenesis